Rival reputations : coercion and credibility in US-North Korea relations - Jackson, Van, 1982- (Cambridge : Cambridge University Press, 2016)
'The Puzzle: In March 2013, the North Korean Central News Agency (KCNA) warned of a'pre-emptive nuclear attack' if the United States convinced the UN Security Council to impose new economic sanctions on North Korea. Despite this warning the Security Council did impose new sanctions at U.S. urging, on March 7. No nuclear attack came. Two weeks later, KCNA released a video of North Korea's leader, Kim Jong Un, discussing a plan for launching nuclear-armed missiles against U.S. bases in the Pacific and the continental United States. The imagery of Kim Jong Un pointing to maps of the United States with arrows outlining missile trajectories was a vivid accompaniment to recent warnings from North Korea's media organs that the North Korean People's Army (KPA) will'destroy not only the military installments ... of South Korea but the ... military bases of the U.S. imperialist aggression forces in the operational theatre of the Pacific.' No attack followed'--Provided by publisher.
'Charting the turbulent history of US-North Korean affairs from the 1960s through to 2010, Rival Reputations explores how past incidents and crises can be relied upon to help determine threat credibility and the willingness of an adversary to resort to violence. Using reputation as the framework, this book answers some of the most vexing questions regarding both US and North Korean foreign policy. These include how they have managed to evade war, why North Korea--a much weaker power--has not been deterred by superior American military power from repeated violent provocations against the United States and South Korea, and why US officials in every administration have rarely taken North Korean threats seriously. Van Jackson urges us to jettison the conventional view of North Korean threats and violence as part of a'cycle' of provocation and instead to recognize them as part of a pattern of rivalry inherent in North Korea's foreign relations. Surveys patterns of crisis, coercion and credibility in US-North-Korea relations from the 1960s through to 2010. Includes historical case studies from archival research. Proposes a new framework for formulating policy toward North Korea'--From publisher's website.
The reputations in rivalry framework -- The USS Pueblo crisis (1968) -- The EC-121 shoot down (1969) -- The Panmunjom crisis (1976) -- The North Korean nuclear crisis (1993-4) -- Nuclear conflict and North-South provocations -- Implications for theory and policy.
Includes bibliographical references (pages 205-213) and index.
Keywords: Crises -- Political aspects -- United States -- History; Crises -- Political aspects -- Korea (North) -- History; Threats of violence -- Political aspects -- Korea (North) -- History; Truthfulness and falsehood -- Political aspects -- Korea (North) -- History; United States -- Foreign relations -- Korea (North); Korea (North) -- Foreign relations -- United States; Korea (North) -- Foreign relations -- Philosophy